ENHANCING HAIRCUTTING SKILLS THROUGH PROJECT-BASED LEARNING: A SURVEY STUDY IN BEAUTY EDUCATION STUDENTS - Clarissia Lovevrani; Erna Setyowati (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
The beauty education sector faces challenges in effectively developing practical skills, particularly in areas like haircutting, which are essential for students’ professional competence. This study aims to explore the impact of Project-Based Learning (PjBL) on enhancing haircutting skills among undergraduate beauty education students. A quantitative explanatory research design was employed, examining the relationship between students' perceptions of PjBL and four dimensions of haircutting performance: progress over time, smoothness of movements, impact of tool transitions, and timing. Data were collected using a structured questionnaire with a five-point Likert scale and analysed through Structural Equation Modelling with Partial Least Squares (SEM-PLS). The results revealed strong internal consistency and convergent validity in the measurement model. Analysis of the structural model demonstrated that PjBL positively influenced all skill dimensions, with the most notable impact on smoothness of movements and timing. These findings underscore the value of PjBL in fostering both cognitive and psychomotor skills in vocational education. This study contributes to the literature by highlighting the benefits of experiential learning and collaboration in developing professional competencies within the beauty education field.